Analisis Dinamika Kelompok pada KWT di Pinggiran Kota (Studi Kasus di KWT 09 Dewi Sri, Desa Cipagalo, Kabupaten Bandung) - Tursina, Marifah; Tridakusumah, Ahmad Choibar (Universitas Galuh, 2025)
Urban fringe areas play a strategic role in supporting food security and community empowerment, including through the presence of Women Farmers Groups (KWT). This study aims to analyze group dynamics in KWT 09 Dewi Sri, a relatively new group actively involved in urban agriculture in Cipagalo Village, Bandung Regency. The research used a case study method with a descriptive approach and scoring analysis on nine elements of group dynamics, involving 21 respondents. The results show that KWT 09 Dewi Sri falls into the dynamic category with a total score of 2,396 out of a maximum of 2,583. This dynamic is reflected in the members’ active participation, cohesiveness, and spirit of mutual cooperation. Despite limited facilities and external support, the group has maintained independence and consistency in its activities. These findings highlight that strong group dynamics are a key factor in ensuring sustainability and strengthening solidarity in urban fringe communities.